ORTHOSTATIC HYPOTENSION. PART 1: DEFINITION, CLASSIFICATION, NATURAL HISTORY - G. A. Golovina; O. N. Zhadan; K. A. Zargaryan; O. A. Kravchenko; N. E. Tripolskaya (Инновационная медицина Кубани)
Orthostatic hypotension (OH) is an excessive decrease of arterial blood pressure when one takes a vertical position. It represents violation of arterial blood pressure circulation at various states and is not an independent disease. OH is associated with an increased risk of the general mortality, incidence of myocardial infarction and cerebral stroke, falling and syncope. We describe definition, classification, prevalence and natural history of OH in this article.